Tourism Promotion and Regional Development in Low-income Developing Countries (The Pakistan Development Review, 2006)
There are not so many papers that the economic effects of tourism are examined in a general equilibrium framework. The features of those papers are that they assume that tourism is regarded as non-tradable goods and services and that tourism is consumed by not only foreign tourists but also domestic residents. However, since our purpose of this paper is to examine the economic effects of tourism promotion on low-income developing countries, we assume that most domestic residents cannot afford to consume tourism, which is considered as a luxury good. Under such assumptions, we examine the effects of two tourism promotion policies on a developing economy. The main result we obtain is that both the policies improve the standard of living for the farmers in a rural region while they worse the standard of living for the workers who are employed in an urban region.